Psychometric liability to psychosis and childhood adversities are associated with shorter telomere length: A study on schizophrenia patients, unaffected siblings, and non-clinical controls. (April 2019) - Çevik, Burcu; Mançe-Çalışır, Öykü; Atbaşoğlu, Eşref Cem; Saka, Meram Can; Alptekin, Köksal; Üçok, Alp; Sırmatel, Burcu; Gülöksüz, Sinan; Tükün, Ajlan; van Os, Jim; Gümüş-Akay, Güvem
Abstract: Compared to the general population, individuals diagnosed with Schizophrenia (SCZ) experience a higher frequency and an earlier onset of chronic medical disorders, resulting in a reduction in life expectancy by an average of 15–25 years. Recently, it has been hypothesized that SCZ is a syndrome of accelerated aging. Childhood adversity was also associated with the pathogenesis and course of SCZ. Our hypothesis was that both SCZ patients and their unaffected siblings would have shorter telomere length (TL) compared to of non-clinical controls. Our additional goals were to determine (1) whether shorter TL correlates with intermediate phenotypes of SCZ (i.e. Psychosis-like symptoms and schizotypal traits); and (2) whether childhood adversities have a moderating role in TL shortening among SCZ and their unaffected siblings. To this end, SCZ patients (n = 100), their unaffected siblings (n = 100) and non-clinical controls (n = 100) were enrolled. The main variables were TL, measured by aTL-qPCR; psychotic-like and schizotypal symptoms, assessed by The Community Assessment of Psychic Experience (CAPE) and the Structured Interview for Schizotypy-Revised (SIS-R), respectively; and childhood adversities evaluated by the Childhood Experience of Care and Abuse (CECA)- Interview . Potentially relevant variables also included in the analyses were: Global Assessment of Functioning (GAF) scores, cognitive performance, and socio-demographic features. In contrast to our hypothesis patients had similar TL when compared to the non-clinical controls. Interestingly, unaffected siblings had longer TL compared to both patients and controls (p < 0.001). Independent from group status a negative correlation was observed between TL and psychotic-like symptoms as rated by the CAPE (p < 0.01). Childhood adversities, especially loneliness between ages 0 and 11 were also negatively associated with TL (p < 0.05). Our findings suggest that psychometric liability to psychosis and childhood adversities may be associated with shorter TL. Unaffected siblings had longer TL, suggesting the potential role of resilience on both the TL and the clinical presentation. These findings must be considered preliminary, calling for larger-scale replication efforts.